2012
DOI: 10.1116/1.4770291
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial strontium titanate films grown by atomic layer deposition on SrTiO3-buffered Si(001) substrates

Abstract: Epitaxial strontium titanate (STO) films have been grown by atomic layer deposition (ALD) on Si(001) substrates with a thin STO buffer layer grown by molecular beam epitaxy (MBE). Four unit cells of STO grown by MBE serve as the surface template for ALD growth. The STO films grown by ALD are crystalline as-deposited with minimal, if any, amorphous SiOx layer at the STO-Si interface. The growth of STO was achieved using bis(triisopropylcyclopentadienyl)-strontium, titanium tetraisopropoxide, and water as the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 60 publications
2
30
0
Order By: Relevance
“…Observing a variation of film density, crystallinity, surface roughness, texture (grain orientation and size), and tetragonality among differently fabricated samples is consistent with observations that film microstructure varies with deposition method, [231] temperature and growth rate [232][233][234], post-deposition treatments [235], strain [236], and stoichiometry . [237] The variation in the BTO films discussed here cannot be used to generally evaluate the different deposition techniques, as none of the deposition has been thoroughly optimized.…”
Section: Structural Characterizationsupporting
confidence: 76%
“…Observing a variation of film density, crystallinity, surface roughness, texture (grain orientation and size), and tetragonality among differently fabricated samples is consistent with observations that film microstructure varies with deposition method, [231] temperature and growth rate [232][233][234], post-deposition treatments [235], strain [236], and stoichiometry . [237] The variation in the BTO films discussed here cannot be used to generally evaluate the different deposition techniques, as none of the deposition has been thoroughly optimized.…”
Section: Structural Characterizationsupporting
confidence: 76%
“…35,36 A four-unit-cell STO buffer layer grown on Si (001) by MBE provided a stable template for the growth of several crystalline oxides, including anatase TiO 2 , STO, BTO, and LAO. [35][36][37][38] Crystalline BTO grown by this method was c-axis oriented, indicating an out-of-plane polarization, with negligible amorphous layer and a sharp STO-Si interface. 38 In this work, we validate the growth of crystalline La:STO films on Si (001) substrates using a combined MBE-ALD growth method.…”
Section: Introductionmentioning
confidence: 99%
“…Both the Sr and Hf metalorganic precursors are commercially available, reactive with water, and have been previously used for ALD. [38][39][40][41][42][43][44][45][46][47][48] Alternating subcycles of Sr and Hf are used to deposit stoichiometric to slightly Sr-rich (56%) films. During each subcycle the metalorganic is dosed for 2 s to ensure complete saturation of the surface, and subsequently purged for 15 s with ultrahigh purity Ar.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work from our group has shown that Sr-rich STO films maintain the perovskite structure, while Ti-rich STO films are more likely to be amorphous. 46 The samples grown for this study varied slightly in cation stoichiometry from 52% to 56% Sr.…”
Section: A Deposition and Crystallization Of Srhfo 3 On Gementioning
confidence: 99%